Fatal Paraquat Poisoning in a Young Female: A case report - Bam, Niraj; Pokhrel, Milan; Dhenga, Sonam; Shrestha, Bibek (Journal of Nepalese Society of Critical Care Medicine, 2026)
Paraquat (PQ) is a highly toxic and lethal herbicide. In countries like Nepal, PQ poisoning is not uncommon. PQ affects the lungs, liver, and kidneys, causing acute failures of these organs due to oxidative stress. In this case report, we describe a 24-year-old female who presented with multiple episodes of vomiting and abdominal pain following suicidal ingestion of 10-15ml of PQ. Initially, the patient was normal clinically, and blood investigations also yielded normal results. However, condition of the patient deteriorated over time, and she passed away due to respiratory distress, acute kidney injury, and acute liver failure while being managed in the intensive care unit.